2009
DOI: 10.1111/j.1467-7652.2009.00435.x
|View full text |Cite
|
Sign up to set email alerts
|

Oil accumulation in leaves directed by modification of fatty acid breakdown and lipid synthesis pathways

Abstract: SummaryPlant oils in the form of triacylglycerol (TAG) are used for food, industrial feedstock and biofuel manufacture. Although TAG is typically harvested from the fruit or seeds of oil crop species, plants can also accumulate small amounts of TAG in the leaves and other vegetative tissues. Here we show that leaf TAG levels can be increased significantly (10-20 fold) by blocking fatty acid breakdown, particularly during extended dark treatments or leaf senescence in the model plant Arabidopsis. Generation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
137
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(148 citation statements)
references
References 39 publications
10
137
1
Order By: Relevance
“…Here, we suggest that there is also a homeostasis between TAG biosynthesis and degradation in higher plants. Experimental evidence has indicated that extended darkness treatment of fatty acid breakdown mutants, such as pxa1, cts2, and acx1acx2, led to the ectopic accumulation of TAG in the leaf (Kunz et al, 2009;Slocombe et al, 2009). The TAG content in naturally senescing leaves of fatty acid breakdown mutants was also increased (Slocombe et al, 2009).…”
Section: There Is a Homeostasis Between Tag Biosynthesis And Degradatmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we suggest that there is also a homeostasis between TAG biosynthesis and degradation in higher plants. Experimental evidence has indicated that extended darkness treatment of fatty acid breakdown mutants, such as pxa1, cts2, and acx1acx2, led to the ectopic accumulation of TAG in the leaf (Kunz et al, 2009;Slocombe et al, 2009). The TAG content in naturally senescing leaves of fatty acid breakdown mutants was also increased (Slocombe et al, 2009).…”
Section: There Is a Homeostasis Between Tag Biosynthesis And Degradatmentioning
confidence: 99%
“…Experimental evidence has indicated that extended darkness treatment of fatty acid breakdown mutants, such as pxa1, cts2, and acx1acx2, led to the ectopic accumulation of TAG in the leaf (Kunz et al, 2009;Slocombe et al, 2009). The TAG content in naturally senescing leaves of fatty acid breakdown mutants was also increased (Slocombe et al, 2009). These data demonstrated that in the wild-type plants, the ectopically accumulated TAG in leaves is broken down rapidly and proved that a TAG homeostasis exists in higher plants.…”
Section: There Is a Homeostasis Between Tag Biosynthesis And Degradatmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a number of studies have established that the oil content can be boosted by the overexpression of individual oil biosynthetic enzymes such as ACYL-COENZYME A:DI-ACYLGLYCEROL ACYLTRANSFERASE1 (DGAT1; Bouvier-Navé et al, 2000) or transcriptional "master" regulators that govern the expression of multiple enzymes in the pathway, such as WRINKLED1 (WRI1), LEAFY COTYLDON1 (LEC1), and LEC2 (Cernac and Benning, 2004;Mu et al, 2008;Andrianov et al, 2010;Sanjaya et al, 2011). In addition, several mutants have been identified that exhibit ectopic oil accumulation (Ogas et al, 1997;Xu et al, 2005;Kunz et al, 2009;Slocombe et al, 2009;James et al, 2010). Among these are pxa1 (peroxisomal ABC transporter1) and cgi58 (comparative gene identification-58), which are associated with lipid catabolism.…”
mentioning
confidence: 99%
“…Various mutants defective in b-oxidation, the glyoxylate cycle, or NADH reduction display peroxisomes clustered near oil bodies after oil bodies are depleted in wild type (Germain et al, 2001;Eastmond, 2007;Pracharoenwattana et al, 2007;Cassin-Ross and Hu, 2014;Rinaldi et al, 2016). Moreover, diphenyl methylphosphonate confers triacylglycerol retention (Brown et al, 2013) similar to sdp1 and pxa1 mutants (Eastmond, 2006;Slocombe et al, 2009;Kelly et al, 2013). The mechanism through which peroxisomal enzyme dysfunction feeds back to prevents triacylglycerol mobilization is unknown.…”
mentioning
confidence: 99%